Efficacy of Essential Oils in Pain: A Systematic Review and Meta-Analysis of Preclinical Evidence - Scuteri, Damiana; Hamamura, Kengo; Sakurada, Tsukasa; Watanabe, Chizuko; Sakurada, Shinobu; Morrone, Luigi Antonio; Rombolà, Laura; Tonin, Paolo; Bagetta, Giacinto; Corasaniti, Maria Tiziana (Frontiers in Pharmacology, 2021)
Background: The demand for essential oils (EOs) has been steadily growing over the years. This is mirrored by a substantial increase in research concerned with EOs also in the field of inflammatory and neuropathic pain. The purpose of this present systematic review and meta-analysis is to investigate the preclinical evidence in favor of the working hypothesis of the analgesic properties of EOs, elucidating whether there is a consistent rational basis for translation into clinical settings. Methods: A literature search has been conducted on databases relevant for medical scientific literature, i.e., PubMed/MEDLINE, Scopus, and Web of Science from database inception until November 2, 2020, following the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) criteria for systematic reviews and meta-analyses. Results: The search was conducted in order to answer the following PICOS (participants/population, interventions, comparisons, outcomes, and study design) question: are EOs efficacious in reducing acute nociceptive pain and/or neuropathic pain in mice experimental models? The search retrieved 2,491 records, leaving 954 studies to screen after the removal of duplicates. The title and abstract of all 954 studies were screened, which left 127 records to evaluate in full text. Of these, 30 articles were eligible for inclusion. Conclusion: Most studies (27) assessed the analgesic properties of EOs on acute nociceptive pain models, e.g. the acetic acid writhings test, the formalin test, and the hot plate test. Unfortunately, efficacy in neuropathic pain models, which are a more suitable model for human conditions of chronic pain, had fewer results (only three studies). Moreover, some methodologies raised concerns in terms of the risk of bias. Therefore, EOs with proven efficacy in both types of pain were corroborated by methodologically consistent studies, like the EO of bergamot, which should be studied in clinical trials to enhance the translational impact of preclinical modeling on clinical pain research.